2017
DOI: 10.1016/j.canlet.2017.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pyruvate carboxylase by 1α,25-dihydroxyvitamin D promotes oxidative stress in early breast cancer progression

Abstract: Maintaining reductive-oxidative (redox) balance is an essential feature in breast cancer cell survival, with cellular metabolism playing an integral role in maintaining redox balance through its supply of reduced NADPH. In the present studies, the effect of 1,25-dihydroxyvitamin D (1,25(OH)2D) on redox balance was investigated in early stages of breast cancer. Treatment with 1,25(OH)2D promoted oxidative stress in MCF10A-ras and MCF10A-ErbB2 breast epithelial cells, as measured by the decreased ratios of NADPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 31 publications
3
55
0
Order By: Relevance
“…Piotrowska A et al report that 1a,25 (OH) 2 D 3 promotes the oxidative damage of H 2 O 2 on human keratinocytes (Piotrowska et al, 2016). In the present study, consistent with enhancement of oxidative stress in breast cancer (Wilmanski et al, 2017), we found that 1a,25(OH) 2 D 3 promoted ROS levels in lung and ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…Piotrowska A et al report that 1a,25 (OH) 2 D 3 promotes the oxidative damage of H 2 O 2 on human keratinocytes (Piotrowska et al, 2016). In the present study, consistent with enhancement of oxidative stress in breast cancer (Wilmanski et al, 2017), we found that 1a,25(OH) 2 D 3 promoted ROS levels in lung and ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our recent studies we observed an enhanced sensitivity to H 2 O 2 upon depletion of PC (Fig 7d and 7e; [29]).…”
Section: Pc Is Required For the Metabolic Plasticity Of Metastatic Brsupporting
confidence: 93%
“…Consistent with our recent studies we observed an enhanced sensitivity to H 2 O 2 upon depletion of PC (Fig. 7d and e ; [ 28 ]).…”
Section: Resultssupporting
confidence: 93%